Commensal Bacillus subtilis from cow milk inhibits Staphylococcus aureus biofilm formation and mastitis in mice. Issue 7 (1st June 2022) - Qiu, Min; Feng, Lianjun; Zhao, Caijun; Gao, Siyuan; Bao, Lijuan; Zhao, Yihong; Fu, Yunhe; Hu, Xiaoyu
Abstract: The colonization and virulence production of Staphylococcus aureus ( S. aureus ), a known pathogen that induces mastitis, depend on its quorum-sensing (QS) system and biofilm formation. It has been reported that Bacillus can inhibit the QS system of S. aureus, thereby reducing S. aureus colonization in the intestine. However, whether Bacillus affects S. aureus biofilm formation and consequent colonization during mastitis is still unknown. In this study, the differences in the colonization of S. aureus and Bacillus were first analyzed by isolating and culturing bacteria from milk samples. It was found that the colonization of Bacillus and S. aureus in cow mammary glands was negatively correlated. Secondly, we found that although Bacillus did not affect S. aureus growth, it inhibited the biofilm formation of S. aureus by interfering its QS signaling. The most significant anti-biofilm effect was found in Bacillus subtili s H28 ( B. subtilis H28). Finally, we found that B. subtilis H28 treatment alleviated S. aureus -induced mastitis in a mice model. Our results rerealed that bovine milk derived commensal Bacillus inhibited S. aureus colonization and alleviated S. aureus- induced mastitis by influencing biofilm formation, suggesting a potential targeted strategy to limit the colonization of S. aureus in vivo . Abstract : Commensal Bacillus subtilis inhibits Staphylococcus aureus colonization and alleviates S. aureus -induced mastitis by influencing biofilm formation.